2020
DOI: 10.1093/nar/gkaa376
|View full text |Cite
|
Sign up to set email alerts
|

G3BP1-linked mRNA partitioning supports selective protein synthesis in response to oxidative stress

Abstract: Abstract Cells limit energy-consuming mRNA translation during stress to maintain metabolic homeostasis. Sequestration of mRNAs by RNA binding proteins (RBPs) into RNA granules reduces their translation, but it remains unclear whether RBPs also function in partitioning of specific transcripts to polysomes (PSs) to guide selective translation and stress adaptation in cancer. To study transcript partitioning under cell stress, we catalogued mRNAs enriched in prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 65 publications
1
59
0
Order By: Relevance
“…As our previous report had shown induction of interferon-dependent pathway upon zinc chelation, we speculate that zinc chelation may trigger the cellular antiviral response by employing both the interferon and the oxidative stress responses which affect the ER. --Alternatively, it has been shown that transient induction of oxidative stress leads to partitioning of mRNA transcripts to stress granules leading to selective translation of genes for stress adaptation [35]. Therefore, induction of oxidative stress at early stages of viral infection may disrupt the formation of ER-derived compartments and/or segregation of viral replication complexes from cellular dsRNA sensing machinery thus leading to inhibition of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…As our previous report had shown induction of interferon-dependent pathway upon zinc chelation, we speculate that zinc chelation may trigger the cellular antiviral response by employing both the interferon and the oxidative stress responses which affect the ER. --Alternatively, it has been shown that transient induction of oxidative stress leads to partitioning of mRNA transcripts to stress granules leading to selective translation of genes for stress adaptation [35]. Therefore, induction of oxidative stress at early stages of viral infection may disrupt the formation of ER-derived compartments and/or segregation of viral replication complexes from cellular dsRNA sensing machinery thus leading to inhibition of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both RNH1 and ANG have been detected in the SG core proteome by high throughput approach [ 47 ] ( Figure 1 G). In another study, RNH1 has been detected with G3BP1, a known SG-nucleator protein, in a stress dependent manner [ 48 ]. What is the significance of the presence of RNH1 in the SG is not yet known.…”
Section: Rnh1 In Translational Regulationmentioning
confidence: 99%
“…They have all been reported to induce the formation of SGs in vitro [ 4 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. It is surmised that SGs are transient triage centers that are designed to help cells to quickly and transiently modify translation to overcome stress and enhance survival, both of which could be used to escape cancer therapies [ 17 , 18 , 19 ].…”
Section: Generalitiesmentioning
confidence: 99%
“…Additionally, SGs sequester untranslated mRNAs concomitantly with the global inhibition of translation [ 17 ]. Some mRNAs, such as chaperone mRNAs, are excluded from the SGs structures, so that they can be preferentially translated during the time of the stress and participate in the proper protein folding and avoid functional defects [ 17 , 19 , 50 ]. By these actions, SGs are described as triage centers for translation of mRNAs during stress exposure [ 17 ].…”
Section: Stress Granules Are Pro-survival Entities At the Cytoplasmentioning
confidence: 99%
See 1 more Smart Citation